Potentiality to Actuality: Quantum Physics Inspires Creative Innovation - Alzeer, Jawad; Benmerabet, Hamid (Jurnal Pijar Mipa, 2025)
Throughout history, humans have demonstrated an extraordinary capacity for creativity and innovation, driving progress and shaping our world. This innate ability to imagine, experiment, and push the boundaries of the possible is central to our identity as free-thinking individuals. To explore the cognitive, psychological, and ethical dimensions that influence the transformative process of translating creative ideas into practical realities, understanding this process as a defining characteristic of human innovation and a reflection of our unique capacity for independent thought. This research utilizes a framework that integrates cognitive psychology, neuroscience, and the principles of quantum physics to analyze the multifaceted dimensions influencing the transformation of creative ideas into reality. This framework will examine cognitive processes, psychological balance, and the alignment of material and non-material values. This research demonstrates that a holistic approach to innovation encompassing material and non-material values is crucial for realising creative potential. This aligns with the principles of quantum physics, where reality emerges from a state of potentiality through conscious observation and interaction. Cultivating free will, critical thinking, and a balanced mentality empowers individuals to harness their creative potential and contribute meaningfully to society. We can unlock human ingenuity and create a brighter future by fostering an environment that encourages independent thought and ethical decision-making.